Flexural behaviour of GGBS concrete beam with steel, hybrid FRP and GFRP bars - et. al., Karikalan A T, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, partial replacement of cement using GGBS content, The percentage of replacement is 5 %, 10%, 15%, 20%, 25%, 30%, 35% and 40%. The content of GGBS will influence on the strength of concrete. The compressive strength, split tensile strength and flexural strength tests are carried out to find the behaviour of concrete. Nowadays the unavailability of river sand is increases. We also study the behavior of GGBS concrete beam using river sand and M sands. GGBS concrete beam using steel bars, hybrid FRP and GFRP bars also incorporated. FRP and GFRP bars are more popular in construction industry. The load vs deflections were measured. In this study shows that the GGBS concrete beam using hybrid FRP are superior to GFRP bars. The GGBS concrete beam using hybrid FRP beam fail by shear and GGBS concrete using GFRP beam fails by both shear and flexure.